Evaluation of soybean germplasm for resistance to soybean rust (Phakopsora pachyrhizi) in Nigeria - Twizeyimana, M.; Ojiambo, P.S.; Ikotun, T.; Ladipo, J.L.; Hartman, G.L.; Bandyopadhyay, Ranajit (Scientific Societies, 2008)
Soybean rust, caused by Phakopsora pachyrhizi, is one of the most important constraints to soybean production worldwide. The absence of high levels of host resistance to the pathogen has necessitated the continued search and identification of sources of resistance. In one set of experiments, 178 soybean breeding lines from the International Institute of Tropical Agriculture were rated for rust severity in the field in 2002 and 2003 at Ile-Ife, Yandev, and Ibadan, Nigeria. Thirty-six lines with disease severity ≤3 (based on a 0-to-5 scale) were selected for a second round of evaluation in 2004 at Ibadan. In the third round of evaluation under inoculated field conditions, 11 breeding lines with disease severity ≤2 were further evaluated for rust resistance at Ibadan in 2005 and 2006. The breeding lines TGx 1835-10E, TGx 1895-50F, and TGx 1903-3F consistently had the lowest level of disease severity across years and locations. In another set of experiments, 101 accessions from the United States Department of Agriculture–Agricultural Research Service and National Agriculture Research Organization (Uganda) were evaluated in the first round in 2005 under inoculated conditions in the screenhouse; 12 accessions with disease severity ≤20% leaf area infected were selected for evaluation in the second round in 2005 and 2006 under inoculated field conditions at Ibadan. Highly significant differences (P < 0.0001) in disease severity were observed among the 101 accessions during this first round of rust evaluation. Significant (P < 0.0001) differences in rust severity and sporulation also were observed among the 12 selected accessions. Accessions PI 594538A, PI 417089A, and UG-5 had significantly (P < 0.05) lower disease severity than all other selected accessions in both years of evaluation, with rust severities ranging from 0.1 to 2.4%. These results indicate that some of the breeding lines (TGx 1835-10E, TGx 1895-50F, and TGx 1903-3F) and accessions (PI 594538A, PI 417089A, and UG-5) would be useful sources of soybean rust resistance genes for incorporation into high-yielding and adapted cultivars.